Hop, bunny! : explore the forest - Neuman, Susan B. (Washington, D.C. : National Geographic, 2014)
Hop Bunny! uses simple vocabulary and fun pictures to capture the interest and help develop the skills of beginning readers. The cuteness, humor, and fun information make this new reading experience a treat.
Keywords: Forests and forestry -- Juvenile literature; Forest animals -- Juvenile literature; Rabbits -- Juvenile literature; Forests and forestry; Forest animals; Rabbits